Chronic Treatment With Imipramine Inhibits Cell Growth and Enhances Serotonin 2C Receptor mRNA Expression in NG 108-15 Cells - Monrudee Sukma; Michihisa Tohda; Hiroshi Watanabe (Elsevier, 2003)
We previously reported that NG108-15 cells contain intrinsic serotonin 2C receptor (5-HT2CR). The effects of imipramine, a 5-HT2CR antagonist, on cell growth, cell viability, and the 5-HT2CR mRNA level were investigated in this study. Repeated treatment with imipramine at concentrations of 1 - 10 μM for 5 days inhibited cell growth in a concentration-dependent manner without affecting cell viability. In addition, the level of 5-HT2CR mRNA was elevated. At 30 μM, imipramine significantly reduced cell viability. Our findings suggest that the effect of imipramine on neuronal growth may be related to its effects on 5-HT2CR.